Digital vertigo therapy: study protocol for a confirmatory randomized controlled trial in patients with vestibular vertigo - Markus Wirth; Jannik Pieper; Ulrike Heller; Michael Bulitta; Daniel Schmitz; Barbara Wollenberg; Hubert Löwenheim; Stephan Wolpert (Trials)
Abstract Background Vestibular vertigo is one of the leading causes of disability. The clinical standard of care for vestibular vertigo includes physical activity producing central vestibular compensation (CVC). Home exercises are considered an integral part of physical therapy. However, a reliable solution is still needed to support the regular and correct execution of home exercises. For this purpose, VH-90-D DiGA was developed, which is a digital therapeutic (DTx) for multimodular in-home therapeutic training. Objective The purpose of this study is to assess the clinical efficacy and safety of a vestibular health app for patients with vestibular vertigo. Methods A randomized group-controlled single-blinded clinical trial (RCT) has been designed. Patients will be randomly assigned to one of two treatment groups and the endpoints examined in a pre-determined order. The experimental group receives the DTx (around 15 min/daily for 90 days), and the control receives physiotherapy according to the German statutory health care plan (usually 6 × 20 min of live physiotherapy). The primary outcome will be vertigo intensity measured using the German version of the validated Vertigo Symptom Scale-short form VSS-sf-VER (0–32 score points). Evaluation is performed after 2, 6, and 12 weeks. Primary outcomes are determined by measuring the group differences of the VSS-sf-score point changes from baseline to week twelve. Including dropouts, the sample size has been determined to be 2 × 100. Expected results It is expected that therapy with the DTx will be statistically superior to physiotherapy in terms of effect size. Discussion This trial protocol marks a confirmatory RCT (GEVE II) to investigate the efficacy and safety of a digital vertigo treatment. The planned RCT is based on a series of primary and secondary efficacy variables. Examination of the endpoints in a pre-determined order ensures the rigor of confirmatory statistics and addresses the challenge of multiplicity. This sequential testing continues until significance is achieved. However, if a specific variable fails to reach significance, subsequent variables will be explored solely on a descriptive basis. Trial registration German National Registry of Clinical Studies (DRKS00028026), a WHO ICRTP registry. Registered on December 12, 2023.